Negative electrode and secondary battery including the same

By using carbon-type active material particles of natural graphite and amorphous carbon material in the negative electrode active material, and combining carbon nanotubes with an average length of 1 μm to 12 μm, the electrode adhesion of natural graphite negative electrode active material in the prior art is solved. The problem of low and deterioration of battery life characteristics achieves higher battery capacity and better high-temperature storage characteristics.

CN113728459BActive Publication Date: 2025-02-25LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080031317.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-29
Filing Date
2020-05-29
Publication Date
2025-02-25
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

When using natural graphite as the negative electrode active material, the prior art has problems such as low electrode adhesion, insufficient capacity, deterioration of battery life characteristics and high temperature storage characteristics.

Method used

Carbon-based active material particles including natural graphite and amorphous carbon-based materials are used as the negative electrode active material, and carbon nanotubes having an average length of 1 μm to 12 μm are used as the conductive agent to form an excellent conductive network.

Benefits of technology

By reducing side reactions of the electrolyte and suppressing the volume expansion of the negative electrode, the battery life characteristics and high-temperature storage characteristics are significantly improved, while improving the adhesion of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003319488700000151
    Figure GDA0003319488700000151
Patent Text Reader

Abstract

The present invention relates to a negative electrode and a secondary battery comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode active material and a conductive material, the negative electrode active material comprises carbon-based active material particles containing natural graphite and amorphous carbon-based materials, and the specific surface area of ​​the carbon-based active material particles is 1.4 m 2 / g~2.3m 2 / g, and the conductive material comprises carbon nanotubes with an average length of 1 to 12 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority from Korean Patent Application No. 10-2019-0063108, filed on May 29, 2019, the disclosure of which is incorporated herein by reference. Technical Field

[0004] The present invention relates to a negative electrode and a secondary battery comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode active material and a conductive agent, wherein the negative electrode active material comprises carbon-based active material particles containing natural graphite and amorphous carbon-based materials, and the carbon-based active material particles have a diameter of 1.4 m 2 / g~2.3m 2 / g, and the conductive agent comprises carbon nanotubes with an average length of 1 μm to 12 μm. Background Art

[0005] Due to the rapid increase in the use of fossil fuels, the demand for the use of alternative energy or clean energy has increased, and as part of this trend, the most actively researched field is the field of power generation and storage using electrochemical reactions.

[0006] At present, a typical example of an electrochemical device utilizing electrochemical energy can be a secondary battery, and the trend is that its application field is getting larger and larger. In recent years, with the increase in technological development and demand for portable devices such as portable computers, mobile phones and cameras, the demand for secondary batteries as energy sources has increased significantly. Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode comprises a negative electrode active material in which lithium ions released from the positive electrode are embedded and deintercalated, and a graphite-based active material such as natural graphite or artificial graphite can be used as the negative electrode active material.

[0007] Artificial graphite is advantageous for battery life characteristics and high-temperature storage characteristics, but has problems of low electrode adhesion and high price.

[0008] The advantage of natural graphite is that it has high electrode adhesion and can increase the capacity of the battery. However, because natural graphite has a plurality of internal voids, the side reaction between the electrolyte and the natural graphite occurs excessively, thereby excessively generating gas in the battery. Moreover, during the charge and discharge of the battery, the volume of the natural graphite increases excessively. As a result, the high temperature storage characteristics and life characteristics of the battery are deteriorated due to the above reasons.

[0009] In order to overcome these limitations, a technique of providing an amorphous carbon coating on conventional natural graphite has generally been used. The amorphous carbon coating is made of asphalt or the like. However, in this case, it is difficult to maintain a high charge / discharge capacity, and there is a limitation in that the life characteristics and high-temperature storage characteristics of the battery are not improved much.

[0010] Therefore, there is a need for a negative electrode capable of improving life characteristics and high-temperature storage characteristics of a battery while obtaining advantages of improving adhesion and capacity of an electrode by using natural graphite. Summary of the invention

[0011] Technical issues

[0012] One aspect of the present invention provides a negative electrode having high electrode adhesion and capacity by using natural graphite and improving life characteristics and high-temperature storage characteristics of a battery, and a secondary battery including the same.

[0013] Technical Solution

[0014] According to one aspect of the present invention, there is provided a negative electrode, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode active material and a conductive agent, wherein the negative electrode active material comprises carbon-based active material particles containing natural graphite and amorphous carbon-based materials, and the carbon-based active material particles have a diameter of 1.4 m 2 / g~2.3m 2 / g, and the conductive agent comprises carbon nanotubes with an average length of 1 μm to 12 μm.

[0015] According to another aspect of the present invention, a secondary battery including the negative electrode is provided.

[0016] Beneficial Effects

[0017] According to the present invention, because the negative electrode contains natural graphite and contains carbon-based active material particles with a low specific surface area as the negative electrode active material, the side reaction of the electrolyte can be reduced and the volume expansion of the negative electrode can be suppressed, thereby improving the life characteristics and high temperature storage characteristics of the battery. In addition, the electrode adhesion can be improved due to the characteristics of natural graphite. In addition, because the negative electrode contains carbon nanotubes with a specific length as a conductive agent, while improving the manufacturing efficiency of the battery and the battery, even when the volume of the negative electrode changes due to the charging and discharging of the battery, the excellent conductive network between the carbon-based active material particles and the carbon nanotubes can be maintained, thereby maximizing the life characteristics and high temperature storage characteristics of the battery and the adhesion of the electrode. DETAILED DESCRIPTION

[0018] Hereinafter, the present invention will be described in more detail to enable a clearer understanding of the present invention.

[0019] It will be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it will also be understood that the words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant fields and technical concepts of the present invention, based on the principle that the inventor can appropriately define the meanings of the words or terms to best explain the present invention.

[0020] The terms used herein are for the purpose of describing specific exemplary embodiments only and are not intended to limit the present invention.In the specification, unless otherwise indicated, a term in the singular form may include a plural form.

[0021] It will be further understood that when used in this specification, the terms "comprises", "comprising" or "having" indicate the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.

[0022] In this manual, the expression "D 50 " can be defined as the particle size at which the cumulative volume is 50% in the particle size distribution curve (curve of a graph of particle size distribution). For example, D 50 This can be measured using laser diffraction, which can generally measure particle sizes ranging from submicrometers to several millimeters, and can obtain highly reproducible and high-resolution results.

[0023] <Negative electrode>

[0024] The negative electrode according to an embodiment of the present invention comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode active material and a conductive agent, wherein the negative electrode active material comprises carbon-based active material particles containing natural graphite and amorphous carbon-based materials, and the carbon-based active material particles have a diameter of 1.4 m 2 / g~2.3m 2 / g, and the conductive agent may include carbon nanotubes having an average length of 1 μm to 12 μm.

[0025] The negative electrode may include a negative electrode active material layer.

[0026] The negative electrode active material layer may include a negative electrode active material and a conductive agent.

[0027] The negative electrode active material may include carbon-based active material particles.

[0028] The carbon-based active material particles may include natural graphite and an amorphous carbon-based material. Specifically, the carbon-based active material particles may include natural graphite and an amorphous carbon-based material disposed on the natural graphite.

[0029] The natural graphite may be formed by a spheroidization process of flaky natural graphite. Therefore, unlike conventional flaky natural graphite, the natural graphite may have a shape close to a sphere. For this reason, since the carbon-based active material particles may expand in volume in all directions during charging and discharging of the battery and the insertion and extraction of lithium may be easy, the life characteristics, high temperature storage characteristics, and fast charging performance of the battery may be improved.

[0030] The average particle size (D 50 ) may be 5 μm to 30 μm, specifically 6 μm to 28 μm. When the above range is satisfied, the energy density of the negative electrode may be improved.

[0031] The amorphous carbon-based material may be disposed on the natural graphite. Specifically, the amorphous carbon-based material may be present as a coating by being coated on the natural graphite.

[0032] The amorphous carbon-based material plays a role in providing an appropriate bonding force so that natural graphite particles are bonded to each other to form carbon-based active material particles. The amorphous carbon-based material may be at least one carbide selected from the group consisting of tar, asphalt and other organic materials, or may be a carbon-based material formed by using hydrocarbons as a source for chemical vapor deposition.

[0033] The carbide of other organic materials may be: carbide of sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose; and carbide of an organic material selected from a combination thereof.

[0034] The hydrocarbon can be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon or a substituted or unsubstituted aromatic hydrocarbon. The substituted or unsubstituted aliphatic or alicyclic hydrocarbon can include methane, ethane, ethylene, acetylene, propane, butane, butylene, pentane, isobutane or hexane. The substituted or unsubstituted aromatic hydrocarbon can include benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene or phenanthrene.

[0035] The average particle size of the carbon active material particles (D 50 ) may be 5 μm to 30 μm, specifically 6 μm to 28 μm, and more specifically 8 μm to 22 μm. When the above range is satisfied, the energy density of the negative electrode may be improved, and the life characteristics of the battery may be further improved.

[0036] The specific surface area of ​​the carbon active material particles can be 1.4 m 2 / g~2.3m 2 / g, specifically 1.5m 2 / g~2.2m 2 / g, more specifically 1.6m 2 / g~2.0m 2 / g. When the specific surface area is less than 1.4m 2 / g, the capacity of the battery may be significantly reduced because the energy density of the negative electrode is too low. On the contrary, when the specific surface area is greater than 2.3m 2 / g, because the side reaction between the carbon-based active material particles and the electrolyte occurs excessively, the life characteristics and high-temperature storage characteristics of the battery may be deteriorated. The specific surface area can be measured by a Brunauer-Emmett-Teller (BET) measuring instrument.

[0037] The pore volume of the carbon active material particles can be 15 cm 3 / g~25cm 3 / g, specifically 15cm 3 / g~22cm 3 / g. The pore volume is mainly affected by the total volume of pores present in and on the surface of the carbon-based active material particles. Since the above range can be achieved with the technology of controlling the internal pores of the carbon-based active material particles by applying pressure to the carbon-based active material particles, the pore volume of the carbon-based active material particles can be made smaller than the pore volume of conventional carbon-based active material particles to which the technology is not applied. When the pore volume is satisfied, the fast charging performance of the battery can be improved because the path through which lithium ions can move becomes shorter as the amount of internal pores decreases. In addition, the life characteristics of the negative electrode can be improved by suppressing the volume expansion of the negative electrode. The pore volume can be measured by a BET meter.

[0038] The sphericity of the carbon active material particles may be 0.92 to 0.97, specifically 0.93 to 0.96, and more specifically 0.94 to 0.95. When the above range is met, a high-density negative electrode can be prepared, and the negative electrode adhesion (the force to prevent the negative electrode active material from peeling off the negative electrode) is improved.

[0039] The content of the carbon-based active material particles in the negative electrode active material layer may be 85 wt % to 99 wt %, specifically 90 wt % to 98 wt %. When the above range is met, a desired battery capacity may be achieved.

[0040] Although not limited thereto, the carbon-based active material particles may be prepared by the following method: The method of preparing the carbon-based active material particles may include: preparing spherical natural graphite; controlling internal pores of the natural graphite; and disposing an amorphous carbon-based material on the natural graphite.

[0041] In the preparation of spherical natural graphite, the natural graphite can be formed by modifying flaky natural graphite. The natural graphite can be prepared by spheroidizing the flaky natural graphite by rolling or agglomerating the flaky natural graphite. Specifically, the flaky natural graphite can be modified into spherical natural graphite using a spheroidizing device.

[0042] In the control of the internal pores of natural graphite, as a method for controlling the internal pores, a method of filling the internal pores with pitch or a cold isostatic pressing (CIP) method can be implemented. This method can make the internal pores have a small volume. In addition, the specific surface area of ​​the carbon-based active material particles can be controlled by controlling the internal pores.

[0043] Disposing the amorphous carbon-based material on the natural graphite may include performing a heat treatment after mixing the natural graphite having controlled internal pores with the material for forming the amorphous carbon-based material. However, it is not necessarily limited to this method.

[0044] The conductive agent may include carbon nanotubes, which play a role in reducing the resistance of the negative electrode by forming a conductive network between negative electrode active material particles.

[0045] In carbon nanotubes, graphene sheets are cylindrical in shape with nanometer-scale diameters and have sp 2 Bond structure. In this case, the carbon nanotubes can exhibit the properties of a conductor or a semiconductor depending on the structure and the angle of the rolled graphite sheet. Carbon nanotubes can be divided into single-walled carbon nanotube (SWCNT) units, double-walled carbon nanotube (DWCNT) units, and multi-walled carbon nanotube (MWCNT) units according to the number of bonds forming the wall.

[0046] The carbon nanotubes may be single-walled carbon nanotubes. In the case where the carbon nanotubes are single-walled carbon nanotubes, since the single-walled carbon nanotubes have higher crystallinity than double-walled or multi-walled carbon nanotubes, a conductive network may be effectively formed in the negative electrode.

[0047] The average length of the carbon nanotubes may be 1 μm to 12 μm, specifically 1 μm to 10 μm, and more specifically 3 μm to 8 μm. When the average length is less than 1 μm, because the carbon nanotubes cannot fully connect the negative electrode active material particles, the conductive network of the negative electrode cannot be effectively formed, so the life characteristics and high temperature storage characteristics of the battery may be deteriorated. On the contrary, when the average length is greater than 12 μm, because the carbon nanotubes may not be smoothly dispersed in the negative electrode, the conductive network may be unevenly formed, and the life characteristics and high temperature storage characteristics of the battery may be deteriorated. The average length can be confirmed by observing the average value of the length of 100 carbon nanotubes in the negative electrode using a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0048] In the case of using conventional carbon-based active material particles, the average length of the carbon nanotubes must be 15 μm or more to suppress excessive volume expansion. However, for the present invention, since carbon-based active material particles whose specific surface area is controlled to be small are used, the volume expansion of the carbon-based active material particles themselves is not large, thereby reducing the average length of the carbon nanotubes to a level of 1 μm to 12 μm. That is, since carbon-based active material particles are used in combination, carbon nanotubes having an average length of 1 μm to 12 μm used in the present invention can be used.

[0049] The average diameter of the carbon nanotubes may be 1 nm to 10 nm, specifically 3 nm to 8 nm, and more specifically 3.8 nm to 6 nm. When the average diameter is less than 1 nm, the preparation cost increases because the preparation of the carbon nanotubes is difficult. On the contrary, when the average diameter is greater than 10 nm, the manufacturing efficiency of the battery and the battery deteriorates because too much weight of the carbon nanotubes is used to form a conductive network. The average diameter can be confirmed by a method of obtaining the average value of the diameters of 100 carbon nanotubes in the negative electrode by observation using SEM or TEM.

[0050] The carbon nanotubes may be present in the negative electrode active material layer in an amount of 0.01 to 1.0 wt %, and specifically in an amount of 0.01 to 0.8 wt %. When the above range is met, an excellent conductive network may be established in the negative electrode while maintaining a high capacity of the battery.

[0051] The weight ratio of the carbon-based active material particles to the carbon nanotubes may be in the range of 1:0.00010 to 1:0.00105, specifically in the range of 1:0.00011 to 1:0.00102, and more specifically in the range of 1:0.00025 to 1:0.00060. When the above range is satisfied, since a conductive network can be stably formed around the carbon-based active material particles, the life characteristics and high temperature storage characteristics of the battery can be improved.

[0052] The negative electrode active material layer may further include a binder. The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid; and materials whose hydrogen is replaced by lithium (Li), sodium (Na) or calcium (Ca), or various copolymers thereof.

[0053] The pore volume of the negative electrode active material layer can be 20 cm 3 / g~40cm 3 / g, specifically 25cm 3 / g~35cm 3 / g. When the above range is met, the life characteristics and high temperature storage characteristics of the battery can be improved. It is difficult to obtain the above range only by using conventional negative electrode active materials. In other words, the above range means that carbon nanotubes with appropriate lengths and carbon-based active material particles with a small specific surface area can have a strong conductive network on the negative electrode (not easily destroyed by the shrinkage and expansion of the negative electrode). After the BET measurement, the pore volume can be measured by a drawing method using the Barrett-Joyner-Halenda (BJH) model.

[0054] The negative electrode may further include a current collector. The current collector plays a role in supporting the negative electrode active material layer. The negative electrode active material layer may be disposed on one surface or both surfaces of the current collector.

[0055] There is no particular limitation on the current collector as long as it has conductivity without causing adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon; aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. Specifically, transition metals such as copper and nickel that adsorb carbon well can be used as the current collector. The thickness of the current collector can be 6 μm to 20 μm, but the thickness of the current collector is not limited thereto.

[0056] <Secondary Battery>

[0057] A secondary battery according to another embodiment of the present invention may include a negative electrode, and the negative electrode is the same as the negative electrode according to the above-described embodiment.

[0058] Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator disposed between the negative electrode and the positive electrode, and an electrolyte, wherein the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description will be omitted.

[0059] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0060] In the positive electrode, there is no particular limitation on the positive electrode collector as long as it has conductivity and does not cause adverse chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, calcined carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. In addition, the positive electrode collector may generally have a thickness of 3 μm to 500 μm, and may have a surface with fine roughness to improve adhesion to the positive electrode active material. The positive electrode collector may be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0061] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include: a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2 A nickel (Ni) site type lithium nickel oxide represented by the chemical formula LiMn O2 (wherein M is at least one selected from the group consisting of cobalt (Co), manganese (Mn), aluminum (Al), copper (Cu), iron (Fe), magnesium (Mg), boron (B) and gallium (Ga), and c2 satisfies 0.01≤c2≤0.3); 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, chromium (Cr), zinc (Zn) and tantalum (Ta), and c3 satisfies 0.01≤c3≤0.1); and LiMn2O4 in which a portion of Li is replaced by alkaline earth metal ions, but the positive electrode active material is not limited thereto. The positive electrode may be Li metal.

[0062] The positive electrode active material layer may include a positive electrode conductor and a positive electrode binder as well as the positive electrode active material.

[0063] In this case, the positive electrode conductive agent is used to provide conductivity to the electrode, wherein any conductive agent can be used without particular limitation as long as it has electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of the positive electrode conductive agent can be: graphite such as natural graphite and artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; metal powders such as copper powder, nickel powder, aluminum powder and silver powder, or metal fibers; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and a single one or a mixture of two or more thereof can be used.

[0064] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples of the positive electrode binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, and a single one or a mixture of two or more thereof can be used.

[0065] The separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used in secondary batteries, in particular, a separator having high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration can be used. Specifically, porous polymer films, such as porous polymer films prepared from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, can be used; or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed of high melting point glass fibers or polyethylene terephthalate fibers. In addition, a coated separator comprising a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multi-layer structure can be selectively used.

[0066] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.

[0067] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0068] Examples of the nonaqueous organic solvent may be aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxy franc, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0069] Especially, ethylene carbonate and propylene carbonate as cyclic carbonate in carbonate organic solvents are dissociated well with lithium salt in electrolyte due to high dielectric constant as high viscosity organic solvent, thus cyclic carbonate can be preferably used.Because when cyclic carbonate is mixed with low viscosity, linear carbonate of low dielectric constant such as dimethyl carbonate and diethyl carbonate in appropriate proportion, electrolyte with high conductivity can be prepared, so cyclic carbonate and linear carbonate can be more preferably used in combination.

[0070] A lithium salt can be used as the metal salt, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte, wherein as an anion of the lithium salt, for example, any one selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C -、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0071] In the electrolyte, in addition to the above electrolyte components, in order to improve the life characteristics of the battery, prevent the reduction of the battery capacity and improve the discharge capacity of the battery, at least one additive may be further included, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0072] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. Because the battery module and the battery pack include secondary batteries having high capacity, high rate characteristics, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0073] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various variations and changes are feasible within the scope and technical spirit of the present invention. Such variations and changes fall within the scope of the claims contained herein.

[0074] Examples and Comparative Examples

[0075] Example 1: Preparation of negative electrode

[0076] As the negative electrode active material, carbon-based active material particles were used, the carbon-based active material particles comprising spherical (sphericity: 0.95) natural graphite (D 50 :15μm) and an amorphous carbon-based material disposed on the natural graphite. In addition, styrene-butadiene rubber (SBR) was used as a binder, and carboxymethyl cellulose (CMC) was used as a thickener. A carbon nanotube dispersion in which single-walled carbon nanotubes were dispersed in distilled water was prepared.

[0077] Carbon-based active material particles, binder, thickener and carbon nanotube dispersion were added to distilled water and then mixed to prepare negative electrode slurry (solid content 40 wt%). The negative electrode slurry was coated on a 10 μm thick copper foil (collector) and then dried, in which case the temperature of the circulating air was 130°C. Subsequently, the collector coated with the negative electrode slurry was rolled, dried at 130°C for 1 hour in a vacuum oven, and then punched into a sheet with an area of ​​15.2 cm 2 A negative electrode including a negative electrode active material layer was prepared. The total amount of carbon-based active material particles and carbon nanotubes contained in the negative electrode active material layer was 97.5 wt %.

[0078] The specific surface area of ​​the carbon active material particles is 1.8 m 2 / g, the pore volume of carbon active material particles is 20cm 3 / g, D of carbon active material particles 50 The average length of the carbon nanotubes is 15 μm, the average length of the carbon nanotubes is 5 μm, and the weight ratio of the carbon-based active material particles to the carbon nanotubes is 1:0.00050.

[0079] Example 2: Preparation of negative electrode

[0080] In addition to using a specific surface area of ​​2.2m 2 A negative electrode was prepared in the same manner as in Example 1 except that the carbon-based active material particles had an average particle size of 100 μg / g.

[0081] Example 3: Preparation of negative electrode

[0082] In addition to using a pore volume of 25 cm 3 A negative electrode was prepared in the same manner as in Example 1 except that the carbon-based active material particles had an average particle size of 100 μg / cm2.

[0083] Example 4: Preparation of negative electrode

[0084] In addition to using the average particle size (D 50 A negative electrode was prepared in the same manner as in Example 1 except that the carbon-based active material particles were 25 μm in diameter.

[0085] Example 5: Preparation of negative electrode

[0086] A negative electrode was prepared in the same manner as in Example 1 except that carbon nanotubes having an average length of 2 μm were used.

[0087] Example 6: Preparation of negative electrode

[0088] A negative electrode was prepared in the same manner as in Example 1, except that the weight ratio of the carbon-based active material particles to the carbon nanotubes was 1:0.00020.

[0089] Comparative Example 1: Preparation of negative electrode

[0090] In addition to the carbon active material particles with a specific surface area of ​​1.0 m 2 A negative electrode was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgCl2O3 was 0.1447 W / g.

[0091] Comparative Example 2: Preparation of negative electrode

[0092] In addition to the carbon active material particles with a specific surface area of ​​3.0 m 2 A negative electrode was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgCl2O3 was 0.1447 W / g.

[0093] Comparative Example 3: Preparation of negative electrode

[0094] A negative electrode was prepared in the same manner as in Example 1, except that the average length of the carbon nanotubes in the negative electrode was 0.3 μm.

[0095] Comparative Example 4: Preparation of negative electrode

[0096] A negative electrode was prepared in the same manner as in Example 1, except that the average length of the carbon nanotubes in the negative electrode was 20 μm.

[0097] [Table 1]

[0098]

[0099] The specific surface area of ​​the carbon active material particles was confirmed by a BET adsorption instrument (BEL). The average particle size (D 50 ) was confirmed by using a PSD instrument. After the BET measurement, the pore volume of the carbon-based active material particles was measured by a mapping method using the BJH model.

[0100] The average length of the carbon nanotubes corresponds to the average length of 100 carbon nanotubes observed in the SEM image of the negative electrode.

[0101] Experimental Example 1: Evaluation of electrode adhesion

[0102] The electrode adhesion of each negative electrode of Examples 1 to 6 and Comparative Examples 1 to 4 was evaluated by the following method.

[0103] In order to evaluate the adhesion between the copper current collector and the negative electrode active material layer, after each negative electrode prepared in the above embodiments and comparative examples was cut into a predetermined size and fixed on a glass slide, the adhesion was evaluated by peeling the current collector to measure the 90° peel strength. In this case, a universal testing machine (UTM) was used to measure the peel strength.

[0104] Experimental Example 2: Evaluation of battery life characteristics

[0105] Batteries were prepared as follows by using the negative electrodes of Examples 1 to 6 and Comparative Examples 1 to 4.

[0106] The LCO positive electrode active material, the carbon black-based conductive agent, and the PVDF powder binder were mixed in an N-methyl-2-pyrrolidone solvent at a weight ratio of 92:2:6 to prepare a positive electrode slurry.

[0107] The prepared positive electrode slurry was coated on a 20 μm thick positive electrode collector so that the electrode loading (mg / cm 2 ) is 23.4 mg per unit area and dried in a vacuum oven at 130°C for 1 hour, and then the coated positive electrode collector is rolled between rollers heated to 80°C at a pressure of 15 MPa to prepare a positive electrode with a final thickness (collector + active material layer) of 72.5 μm.

[0108] The negative electrode and positive electrode prepared above and the porous polyethylene separator were assembled by using a stacking method, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1:4 (volume ratio), lithium hexafluorophosphate (LiPF6 1 mol), vinylene carbonate (VC) based on the weight of the electrolyte: 0.5 wt %) was injected into the assembled battery to prepare a lithium secondary battery.

[0109] After setting the charging range of the prepared battery to from 0% state of charge (SOC) to 100% SOC, each battery was charged and discharged at a current rate of 0.1C in the 1st cycle, charged and discharged at a current rate of 0.2C in the 2nd cycle, and charged and discharged at 0.5C from the 3rd cycle to the 100th cycle, and then the capacity retention rate of each battery was calculated by the following formula.

[0110] Capacity retention rate (%) = [(discharge capacity after 100th cycle - initial discharge capacity) / initial discharge capacity] × 100

[0111] Experimental Example 3: Evaluation of high temperature storage characteristics

[0112] The high-temperature storage resistance increase rate of each negative electrode of Examples 1 to 6 and Comparative Examples 1 to 4 was evaluated by the following method.

[0113] The battery prepared in the same manner as described in Experimental Example 2 was charged at 100% SOC, left to stand for 30 minutes, and then discharged at 2C. In this case, the resistance of each battery was set to the initial resistance. Thereafter, each battery was charged again at 0.5C at 100% SOC, and the battery was subsequently stored in an oven at 60°C. After 4 weeks, the battery was taken out of the oven and left to stand for 4 hours so that the temperature dropped to room temperature, and then the battery was discharged at 2C. After measuring the resistance of the battery in this case, the resistance increase rate of the battery was calculated by the following formula.

[0114] Resistance increase rate (%) = [(resistance after 4 weeks - initial resistance) / initial resistance] × 100

[0115] [Table 2]

[0116] Electrode adhesion (gf / 20mm) Capacity retention rate (%) Resistance increase rate (%) Example 1 41.8 95.9 12.2 Example 2 36.5 94.2 18.0 Example 3 38.2 94.8 16.7 Example 4 32.8 92.3 13.1 Example 5 35.4 93.0 19.1 Example 6 34.2 90.8 18.9 Comparative Example 1 42.3 84.8 21.2 Comparative Example 2 18.5 75.8 28.4 Comparative Example 3 20.2 70.6 26.4 Comparative Example 4 31.5 81.8 25.1

[0117] Referring to Table 2, it can be understood that the capacity retention rate and resistance increase rate of the negative electrode of the embodiment are significantly better than those of the comparative example, and the electrode adhesion of the negative electrode of the embodiment is higher than that of the electrode adhesion of comparative examples 2, 3 and 4. The negative electrode of the embodiment includes a specific surface area satisfying 1.4 m 2 / g~2.3m 2 / g of carbon-based active material particles and carbon nanotubes with an average length of 1 μm to 12 μm.

Claims

1. A negative electrode for a secondary battery, the negative electrode comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode active material and a conductive agent, wherein the negative electrode active material comprises carbon-based active material particles containing natural graphite and amorphous carbon-based materials, The carbon active material particles have a diameter of 1.4 m 2 / g~2.3m 2 / g specific surface area, The natural graphite has an average particle size D of 5 μm to 30 μm. 50 , The conductive agent comprises carbon nanotubes having an average length of 1 μm to 12 μm, and The carbon nanotubes have an average diameter of 1 nm to 8 nm.

2. The negative electrode for a secondary battery according to claim 1, wherein the carbon-based active material particles have a particle size of 1.6 m 2 / g~2.0m 2 / g specific surface area.

3. The negative electrode for a secondary battery according to claim 1, wherein the carbon-based active material particles have an average particle size D of 5 μm to 30 μm. 50 .

4. The negative electrode for a secondary battery according to claim 1, wherein the carbon-based active material particles have a diameter of 15 cm 3 / g~25cm 3 / g pore volume. 5 . The negative electrode for a secondary battery as claimed in claim 1 , wherein the carbon nanotube is a single-walled carbon nanotube. 6 . The negative electrode for a secondary battery according to claim 1 , wherein a weight ratio of the carbon-based active material particles to the carbon nanotubes is in a range of 1:0.00010 to 1:0.00105. 7 . The negative electrode for a secondary battery as claimed in claim 1 , wherein the carbon-based active material particles have a sphericity of 0.92 to 0.

97.

8. The negative electrode for a secondary battery according to claim 1, wherein the negative electrode active material layer has a thickness of 20 cm 3 / g~40cm 3 / g pore volume.

9. A secondary battery, comprising: The negative electrode for a secondary battery according to claim 1; positive electrode; A separator provided between the positive electrode and the negative electrode for a secondary battery; and Electrolytes.

Citation Information

Patent Citations

  • Semiconductor package structure and semiconductor Module including the same

    KR1020190063108A

  • Anode comprising spherical natural graphite and lithium secondary battery including same

    CN104106160A

  • Lithium-ion rechargeable battery

    CN1574444A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    KR1020130015967A

  • Electrode Slurry for Secondary Battery Containing Two Types of Conductive Materials and Secondary Battery Comprising the Same

    KR1020170117980A